Effect of aqueous extract of Asparagus officinalis on some Antioxidants in Rats Exposed to Oxidative Stress induced by Hydrogen peroxide - Yaser A.M. Sulaiman; , Al-saeedy, Khalid. A. H.; Moayad M.Y. Al-Anzy (Tikrit Journal of Pure Science)
The current study dealt with using  of hydrogen peroxide with 0.5% with drinking water to induce state of oxidative stress in male rats and estimate the ability of different concentrations of the aqueous extract of asparagus officinalis to reduce the effects of oxidative stress during periods 0,15,30 days by measuring the following parameters in serum: Glutathione(GSH), Malondialdehyde (MDA), the activity of super oxide dismutase enzyme (SOD) and the peroxynitrate radical (ONOO).